A detection method integrating modal deflection curvature difference and natural frequency for structural stiffness degradation. (November 2022) - Wang, Lei; Chen, Rui; Dai, Lizhao; Huang, Ke; Zhang, Jiabin; Tang, Cui
Highlights: A detection method is proposed to realize the structural damage localization and quantification. Numerical studies are performed to demonstrate the proposed damage detection method. An experiment is performed to evaluate the proposed damage detection method on site. Abstract: A detection method integrating modal deflection and natural frequency is proposed to locate and quantify the damage of the beam. A damage identification index using modal deflection curvature difference is developed to locate damage. Note that the modal deflection is derived from the flexibility matrix and virtual force. A damage quantification equation is established by the transfer matrix method, which includes the parameters of natural frequencies, damage coefficients and damage location. Since the damage location parameters are determined by the proposed damage identification index, the damage coefficients of the damaged segments can be determined from the natural frequencies according to the damage quantification equation. The proposed damage detection method is verified numerically and experimentally. The results indicate that the proposed method can well locate and quantify the local damage of beams, especially for the beams with non-uniform damage degradation. The proposed damage localization index is more appropriate to locate damage than the index using modal flexibility curvature (MFC) or modal flexibility curvature matrix (MFCM).